Methods and tools for evaluating motivational factors of high-tech enterprises specialists in Russia and Iran - A. J. Bonyani (Управление)
The article is devoted to the actual problem of determining the motivational factors of high-tech enterprises specialists in Russia and Iran. Labour resources are the main resource for any enterpris, but for enterprises engaged in the production of high-tech products, labour resources are the most important resource on which not only quantitative, but also qualitative indicators of the enterprise depend. In this regard, the article considers methods and tools for evaluating motivational factors of high-tech enterprises specialists. The necessity of studying the motives of specialists in order to increase their productivity and achieve the overall goals of the enterprise has been substantiated. It has been determined that motives and needs have a diﬀerent nature, their study contributes to a qualitative approach to the motivation system development for employees of the enterprise. The paper carries out a comparative characteristic of the existing systems of employees’ motivation in Iran and Russia, which are based on the requirements of compliance with the labour legislation of the analysed countries. The fundamental diﬀerences between the applied incentives of employees of enterprises and organisations in Russia and Iran, which are based on nationality and culture, have been determined. The data presented in the study can be used in the employment of Russians in Iran, taking into account the speciﬁc features of working conditions.